A Faculdade de Medicina de Ribeirão Preto - USP (1948 - 1975) - Araújo, Marcelo José (Universidade Federal de São Carlos, 2007)
This work carries through a historical survey of the creation process, installation and development of the Faculdade de Medicina de Ribeirão Preto da Universidade de São Paulo (FMRP-USP) in the period from 1948 the 1975. Part of its ampler historical context until the its more specific approach, that is, to its constituent characteristics, elements and, over all, to its social meaning. The text initiates approaching the historical antecedents of the medicine in Brazil in the end of century XIX and the beginning of the XX, giving has detached to the controls of the endemic diseases and its protagonists, the creation of the Faculdade de Medicina de São Paulo and the necessity of installation of a College of Medicine in the interior of the state of São Paulo. After that, it approaches the circumstances of the creation, installation and of the developing of the FMRP, detaching the didactic structure of the course, the faculty, the student body, the employees, the first university entrance examination, your discipline them and the departments, the developed research, the Hospital of the Clinics etc. These circumstances meet inserted in the First Part of the work. In the Second Part, in turn, are characterized and analyzed some considered problems important to help to better understand the relation between the FMRP and the society that produced it and it molded it. Beginning all this historical survey, the Theoretical Reference whose estimated beddings and had given support to the research; after all, as well as a teacher conducts an orchestra searching harmony between its integrant ones, the theoretical reference served as guide maker for the success of the set.
Keywords: Educação; Ribeirão Preto (SP) - instituição escolar - Faculdade de Medicina da Universidade de São Paulo; História; Filosofia; School Institution; History; Philosophy and Education; CIENCIAS HUMANAS::EDUCACAO